Vpr protein of human immunodeficiency virus type 1 forms cation-selective channels in planar lipid bilayers. - Piller, S C (1996)
A small (96-aa) protein, virus protein R (Vpr), of human immunodeficiency virus type 1 contains one hydrophobic segment that could form a membrane-spanning helix. Recombinant Vpr, expressed in Escherichia coli and purified by affinity chromatography, formed ion channels in planar lipid bilayers when it was added to the cis chamber and when the trans chamber was held at a negative potential. The channels were more permeable to Na+ than to Cl- ions and were inhibited when the trans potential was made positive. Similar channel activity was caused by Vpr that had a truncated C terminus, but the potential dependence of channel activity was no longer seen. Antibody raised to a peptide mimicking part of the C terminus of Vpr (AbC) inhibited channel activity when added to the trans chamber but had no effect when added to the cis chamber. Antibody to the N terminus of Vpr (AbN) increased channel activity when added to the cis chamber but had no effect when added to the trans chamber. The effects of potential and antibodies on channel activity are consistent with a model in which the positive C-terminal end of dipolar Vpr is induced to traverse the bilayer membrane when the opposite (trans) side of the membrane is at a negative potential. The C terminus of Vpr would then be available for interaction with AbC in the trans chamber, and the N terminus would be available for interaction with AbN in the cis chamber. The ability of Vpr to form ion channels in vitro suggests that channel formation by Vpr in vivo is possible and may be important in the life cycle of human immunodeficiency virus type 1 and/or may cause changes in cells that contribute to AIDS-related pathologies.